The impact of port transport-logistics infrastructure and LPI for economic growth : on the example of landlocked countries - Duzbaievna Sharapiyeva, Madina (Array, 2019)
For this study, carried out as an empirical study, 37 landlocked countries have been selected. And a broader economic impact on the national economy, on the quality of the port infrastructure and logistics efficiency has been considered as well as investments on creating a high quality port infrastructure and its contribution to the economy, often questioned by politicians, investors and general public. The Structural Equation Model (SEM) has been used for providing empirical data about a significant economic impact on the port infrastructure quality and logistics efficiency. However, some countries that do not have access to the sea are not, according to international agreements, inferior to other countries in terms of economic growth.